The Influences of Productive Zakah Mentoring To Saving Behavior and The Prosperity of Poor Housewife - Rizky Andriati; Nurul Huda (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2015)
The purpose of this study was to determine the influences of productive zakah mentoring to the saving attitude, the confidence of saving ability, the saving behavior and the prosperity of poor housewives which become partners of Masyarakat Mandiri Dompet Dhuafa. This is a quantitative research using Structual Equation Modelling. The respondents are 115 poor housewives in Parung, Bogor, West Java; Cipinang, East Jakarta; Tanjung Pasir, Tangerang, Banten; and Bantar Gebang, Bekasi, West Java. The variables that used on this research are the mentoring of zakah productive, saving attitude, saving behavior, and prosperity. The result showed that the mentoring of productive zakah program has significant influence for the saving attitude and saving behavior. Saving behavior also affects significantly the prosperity of poor housewivesDOI: 10.15408/aiq.v7i2.1698